Sonographic Parameters for Prediction of Miscarriage: Role of 3‐Dimensional Volume Measurement. (31st August 2015) - Wie, Jeong Ha; Choe, Suyearn; Kim, Sa Jin; Shin, Jong Chul; Kwon, Ji Young; Park, In Yang
Abstract : Objectives: To evaluate the value of volume measurement using 3‐dimensional sonography for prediction of miscarriage. Methods: We prospectively enrolled 188 singleton pregnant women at 5 to 9 weeks' gestation. The 3‐dimensional sonographic gestational sac volume and yolk sac volume were measured together with the fetal heart rate, gestational sac diameter, and yolk sac diameter. For each sonographic parameter, nomograms were created; z scores were calculated for each measurement, and the values were compared between miscarriage and ongoing pregnancy groups. Sonographic parameters for prediction of miscarriage were evaluated by multivariate analysis, and the screening performance was assessed by a receiver operating characteristic curve. Results: Among the 188 pregnancies, 30 (16.0%) had miscarriage. Multivariate analysis showed that fetal heart rate below the 5th percentile (odds ratio, 6.43), gestational sac diameter below the 5th percentile (odds ratio, 4.87), gestational sac volume below the 5th percentile (odds ratio, 5.25), and yolk sac diameter below the 2.5th or above the 97.5th percentile (odds ratio, 15.86) were significant predictors of miscarriage ( P = .018; P = .018; P = .033; and P < .001, respectively). At a false‐positive rate of 30%, the detection rate for miscarriage in screening by a combination of fetal heart rate, gestational sac diameter, gestational sac volume, and yolk sac diameter was 77.8%. Conclusions: A small‐for‐gestational‐age gestational sac volume is a significant sonographic predictor of miscarriage, as are fetal bradycardia, a small gestational sac diameter, and a small or large yolk sac diameter.